Implications of Charcoal Briquette Produced by Local Communities on Livelihoods and Environment in Nairobi- Kenya - Njenga, M.; Yonemitsu, A.; Karanja, N.; Iiyama, M.; Kithinji, J.; Dubbeling, M.; Sundberg, C.; Jamnadass, R. (International Journal of Renewable Energy Development, 2013)
The residents of Nairobi, Kenya, use 700 tonnes of charcoal per day, producing about88 tonnes of charcoal dust that is found in most of the charcoal retailing stalls that is disposed of inwater drainage systems or in black garbage heaps. The high costs of cooking fuel results in poorhouseholds using unhealthy materials such as plastic waste. Further, poor households are opting tocook foods that take a short time to prepare irrespective of their nutritional value. This articlepresents experiences with community self-help groups producing charcoal fuel briquettes fromcharcoal dust in poorer nieghbourhoods of Nairobi for home use and sale. Households thatproduced charcoal fuel briquettes for own use and those that bought them saved 70% and 30% ofmoney spent on cooking energy respectively. The charcoal fuel briquettes have been found to beenvironmentally beneficial since they produce less smoke and increase total cooking energy bymore than 15%, thereby saving an equivalent volume of trees that would be cut down for charcoal.Charcoal briquette production is a viable opportunity for good quality and affordable cooking fuel.Bioenergy and waste management initiatives should promote recovery of organic by-products forcharcoal briquette production.